2020
DOI: 10.3390/medicina56060276
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Self-Regulation Module and Mobile Application to Enhance Treatment Outcome for Patients with Acne

Abstract: Background and Objectives: Acne, an inflammatory disorder of the pilosebaceous unit associated with both physiological and psychological morbidities, should be considered a chronic disease. The application of self-regulation theory and therapeutic patient education has been widely utilized in different health-related areas to help patient with a chronic disease to attain better behavioral modification. The present study aims at investigating the treatment efficacy of combining a self-regulation-based patient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(30 reference statements)
0
8
0
2
Order By: Relevance
“…Both studies reported significant improvement in CADI scores following intervention, with the greatest improvement in the text‐message group. Additionally, one study reported the impact of patient education alongside the use of a mobile application on the enhancement of treatment outcome 59 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies reported significant improvement in CADI scores following intervention, with the greatest improvement in the text‐message group. Additionally, one study reported the impact of patient education alongside the use of a mobile application on the enhancement of treatment outcome 59 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, one study reported the impact of patient education alongside the use of a mobile application on the enhancement of treatment outcome. 59 Four studies [60][61][62][63] reported using phototherapy in treating acne. Two studies reported CADI scores showing a significant improvement following intervention and two gave descriptive accounts of improvement in CADI score; however, P-values were not always reported.…”
Section: Other Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we argue that the contents of this paper on trichotillomania are likely to be of relevance to the dermatology community, justifying its inclusion in this systematic review. Furthermore, we identified several papers at the full text screening stage which were of some relevance to this review, but these were excluded on the basis that they involved people as young as 12 (15,(87)(88)(89)(90) and 16 (91,92) years old and pooled the results (93)(94)(95)(96), preventing us from extrapolating the results specific to our population of interest. It is possible that we missed information related to the review questions by excluding these papers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Many lesions such as, comedones, papules, pustules, nodules, and cysts can be seen together in patients, as well as causing scarring and pigmentation changes. AV may be associated with much physiological and psychological comorbidity in patients 1 …”
Section: Introductionmentioning
confidence: 99%